2000
DOI: 10.1093/bja/85.6.907
|View full text |Cite
|
Sign up to set email alerts
|

Sex and oestrous cycle differences in visceromotor responses and vasopressin release in response to colonic distension in male and female rats anaesthetized with halothane †

Abstract: Visceromotor responses and vasopressin release before and after colonic visceral distension were compared between male (n=5 (n=4 for vasopressin)) and female rats and between females during the oestrous cycle (proestrus n=6, oestrus n=5, metestrus n=5, diestrus n=6) at a controlled depth of anaesthesia. Pre-stimulation vasopressin and blood pressures demonstrated oestrous cycle variability. The mean (SEM) colonic balloon pressure triggering visceromotor responses was significantly higher in males (64 (4) mm Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
35
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 8 publications
8
35
0
Order By: Relevance
“…We have previously reported that the magnitude of the visceromotor response (a suprathreshold response) does not fluctuate with the estrous cycle (Ji et al 2006), although the threshold to evoke the visceromotor response does fluctuate across the estrous cycle (Sapsed-Byrne et al, 1996;Holdcroft et al 2000). These data and our previous reports that E2 replacement reverses the antinociceptive effect of ovariectomy (Ji et al, 2003b;Ji et al, 2005), suggests female gonadal hormones modulate visceral nociceptive processing.…”
Section: Discussionsupporting
confidence: 58%
“…We have previously reported that the magnitude of the visceromotor response (a suprathreshold response) does not fluctuate with the estrous cycle (Ji et al 2006), although the threshold to evoke the visceromotor response does fluctuate across the estrous cycle (Sapsed-Byrne et al, 1996;Holdcroft et al 2000). These data and our previous reports that E2 replacement reverses the antinociceptive effect of ovariectomy (Ji et al, 2003b;Ji et al, 2005), suggests female gonadal hormones modulate visceral nociceptive processing.…”
Section: Discussionsupporting
confidence: 58%
“…It is possible that alterations in the pattern of oscillations in PER2 are associated with changes in neuronal response to different types of inputs, with the processing of information within these structures, and͞or with the modulation of their output pathways. For example, cyclic variation in GABAergic tone or in neuropeptide content associated with changes in PER2 expression within the BNST-OV and CEA could contribute to the variation in stress responsivity observed across the estrous cycle (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will need to address the relative importance of V 3 receptor antagonism of hypothalamic and extrahypothalamic AVP signaling in the development and expression of chronic visceral hyperalgesia. Although V 3 receptors are also expressed in the gastrointestinal tract (38), AVP is released by CRD (21), and peripherally administered AVP or AVP analogs exert significant effects on colonic secretomotor functions in animals and humans (44,45,54), a peripheral effect of SSR149415 on visceral afferent pathways explaining the observed pattern of antihyperalgesia is unlikely. Similarly, even if the antagonist had exerted a modulatory effect on colonic tone (which was not evaluated in the present study), the employed barostat technique would have compensated for such a peripheral effect.…”
Section: Effect Of Repeated Dosing With Ssr149415 On the Development mentioning
confidence: 99%
“…For example, preclinical and clinical data suggest that AVP signaling may be involved in stress-and CRF-induced modulation of intestinal motility (10,21,54). However, a role of AVP/V 3 signaling in stress-induced visceral hyperalgesia has not been demonstrated.…”
mentioning
confidence: 99%